Groundwater level influence on liquefaction potential at Pombewe housing site, Sigi regency, Central Sulawesi - Anar Halimatussaadiyah; Rifa’i Ahmad; Faris Fikri (E3S Web of Conferences, 2024)
The September 28, 2018, earthquake in Palu, Central Sulawesi, caused liquefaction and destroyed at least 3,720 houses. Therefore, it is necessary to consider the potential of liquefaction in choosing a residential location, especially in liquefaction-prone zones. The parameters of soil type, seismicity, and the groundwater table as a determinant of the saturation level determine liquefaction potential. The research aims to see the influence of groundwater level parameters in increasing the liquefaction potential when other parameters are met. The study was conducted at the Pombewe permanent housing site, Sigi Regency, Central Sulawesi. This shelter is an official relocation area for victims of the 2018 earthquake. Preliminary data stated that the location is safe from liquefaction potential because it has a deep groundwater table. The study used the CPT-based liquefaction triggering procedure method by Boulanger and Idriss and assumed that the groundwater table at the site was shallow. The Liquefaction Potential Index determines the potential liquefaction level. The results show that the area under review will only experience liquefaction if the groundwater table is above 1.0-11.6 meters (LPI>0). If the water table rises above that depth, the LPI value increases to 1.6x10-9 – 0.44. Thus, the water table is a determining parameter in analyzing the liquefaction potential of an area.